Educational moderation of gender disparities in psychedelic health outcomes - Sean Viña (Academia Mental Health & Well-Being)
While public interest in psychedelics is rising due to their potential effects on mental health, evidence suggests that these associations vary across demographic groups. Notably, prior research indicates that women may experience different outcomes from psychedelic use compared to men. Given that highly educated women tend to have superior health outcomes in general, this study examines whether education modifies the association between Lifetime Classic Psychedelic Use (LCPU) and psychological distress. Using pooled data from the National Survey of Drug Use and Health (NSDUH) (2008–2019) (n = 458,372), this study applies nested Ordinary Least Square Regression (OLS) regression models in Stata 18. Results from three-way interaction terms indicate that while LCPU is associated with higher distress overall, the association varies across education levels. This pattern suggests that rather than universally improving mental health, the effects of psychedelic use depend on key social factors such as education and gender.